Hydrogen peroxide suppresses excitability of gonadotropin-releasing hormone neurons in adult mouse - Rijal, Santosh; Jang, Seon Hui; Cho, Dong Hyu; Han, Seong Kyu (Frontiers in Endocrinology, 2022)
It has been reported that reactive oxygen species (ROS) derived from oxygen molecule reduction can interfere with the cross-talk between the hypothalamic-pituitary-gonadal (HPG) axis and other endocrine axes, thus affecting fertility. Furthermore, ROS have been linked to GnRH receptor signaling in gonadotropes involved in gonadotropin release. There has been evidence that ROS can interfere with the HPG axis and gonadotropin release at various levels. However, the direct effect of ROS on gonadotropin-releasing hormone (GnRH) neuron remains unclear. Thus, the objective of this study was to determine the effect of hydrogen peroxide (H2O2), an ROS source, on GnRH neuronal excitabilities in transgenic GnRH-green fluorescent protein-tagged mice using the whole-cell patch-clamp electrophysiology. In adults, H2O2 at high concentrations (mM level) hyperpolarized most GnRH neurons tested, whereas low concentrations (pM to uM) caused slight depolarization. In immature GnRH neurons, H2O2 exposure induced excitation. The sensitivity of GnRH neurons to H2O2 was increased with postnatal development. The effect of H2O2 on adult female GnRH neurons was found to be estrous cycle-dependent. Hyperpolarization mediated by H2O2 persisted in the presence of tetrodotoxin, a voltage-gated Na+ channel blocker, and amino-acids receptor blocking cocktail containing blockers for the ionotropic glutamate receptors, glycine receptors, and GABAA receptors, indicating that H2O2 could act on GnRH neurons directly. Furthermore, glibenclamide, an ATP-sensitive K+ (KATP) channel blocker, completely blocked H2O2-mediated hyperpolarization. Increasing endogenous H2O2 by inhibiting glutathione peroxidase decreased spontaneous activities of most GnRH neurons. We conclude that ROS can act as signaling molecules for regulating GnRH neuron’s excitability and that adult GnRH neurons are sensitive to increased ROS concentration. Results of this study demonstrate that ROS have direct modulatory effects on the HPG axis at the hypothalamic level to regulate GnRH neuron’s excitabilities.